An agile and cooperative architecture for distributed manufacturing systems - Leitão, Paulo (2010)
World-wide competition among enterprises leads to the need for new systems to perform the control of distributed manufacturing systems, through the integration of information systems and self-organisation features, in order to adapt quickly to the environment changes. This paper presents an agile and cooperative architecture for distributed manufacturing systems based in the multiagent technology which implements some holonic and bionic concepts and supports a new control approach, including the re-engineering phase.